A kind of polypropylene warm edge strip material and preparation method thereof and warm edge strip

Through the raw materials and preparation technology with specific ratios, the problems of unstable bonding, high shrinkage ratio and unstable dimensional during the molding process of polypropylene warm edge strips are solved, and high bonding and low shrinkage rate are achieved And stable size warm edge strip products.

CN119192735BActive Publication Date: 2025-02-07SHENYANG KETONG NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411731558.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-07
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing polypropylene warm edge strips are unstable in the preparation process, the shrinkage ratio is high, and the dimensionality is unstable during the molding process.

Method used

Raw materials with specific ratios include polypropylene, polystyrene, maleic anhydride grafted polypropylene, maleic anhydride grafted hydrogenated styrene-butadiene block copolymer, tackifying resin, inorganic filler and modified nano Cellulose, polypropylene warm edge strips are prepared by mixing, melting, extruding and granulation.

Benefits of technology

It significantly improves the adhesion and peel strength of the warm edge strips to stainless steel, reduces the shrinkage and dimensional instability of the material, and ensures the dimensional stability and high bond strength of the product during the molding process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to a polypropylene warm edge strip material and a preparation method and a warm edge strip, belonging to the technical field of warm edge strips, and is used to solve one of the problems of unstable bonding, high shrinkage ratio, and unstable size during molding of warm edge strips prepared by existing methods. A polypropylene warm edge strip material, according to weight parts, the polypropylene warm edge strip material comprises the following raw materials: 45-65 parts of PP, 10-18 parts of PS, 4-8 parts of maleic anhydride grafted PP, 4-8 parts of maleic anhydride grafted SEBS, 8-12 parts of tackifying resin, 10-20 parts of inorganic filler and 0.2-0.4 parts of lubricant. In the present invention, under the mutual synergy and joint action of each component, it can be ensured that the prepared warm edge strip has excellent bonding with stainless steel and has high peel strength. At the same time, the product has good dimensional stability and a small shrinkage ratio, ensuring that the material is not prone to steel-plastic separation during the molding process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of warm edge strips, in particular to a polypropylene warm edge strip material and a preparation method thereof. Background Art

[0002] Warm edge strips, also known as warm edge spacers, are used as partition materials between double-layer glass in insulating glass. They are processed by hot and cold co-extrusion and make important contributions to the insulation and noise reduction functions of insulating glass. Warm edge strips are mainly made of low thermal conductivity materials. The working principle of warm edge strips is similar to that of thermal insulation strips used in broken bridge windows. The thermal insulation coefficient of warm edge strips is much lower than that of general insulating glass, which can effectively reduce the heat loss of glass and ensure that the temperature difference between the two sides of the glass is not too large, thereby achieving thermal insulation and avoiding condensation on the glass.

[0003] At present, the most common warm edge strips on the market are processed and formed by co-extrusion of stainless steel + polyvinyl chloride (PVC). However, due to the poor environmental performance of PVC and its high thermal conductivity, polypropylene materials with lower thermal conductivity and more environmental protection are gradually favored by the market and researchers in the industry. However, the polarity of polypropylene is poor and it has almost no adhesion to stainless steel. The main process in the market at present is to use adhesives to bond stainless steel. One process is to first coat the adhesive on the surface of the stainless steel and then co-extrude it with the PP material for bonding. The second process is to extrude stainless steel, adhesive, and PP at the same time. The fluidity of the adhesive is poor, and the shrinkage of polypropylene is relatively serious. Therefore, the above two methods are prone to unstable bonding, resulting in the warm edge strip products failing to meet the requirements during use. Therefore, it is very necessary to develop a polypropylene warm edge strip material that has excellent adhesion to stainless steel and good dimensional stability during processing. Summary of the invention

[0004] In view of the above analysis, the present invention aims to provide a polypropylene warm edge strip material and a preparation method and a warm edge strip, so as to solve one of the problems of the warm edge strip prepared by the existing method, such as unstable bonding, high shrinkage ratio, and dimensional instability during molding.

[0005] In a first aspect, the present invention provides a polypropylene warm edge strip, which comprises the following raw materials in parts by weight: polypropylene (PP): 45-65 parts, polystyrene (PS): 10-18 parts, maleic anhydride grafted polypropylene (PP): 4-8 parts, maleic anhydride grafted hydrogenated styrene-butadiene block copolymer (SEBS): 4-8 parts, tackifying resin: 8-12 parts, inorganic filler: 10-20 parts and lubricant: 0.2-0.4 parts.

[0006] Furthermore, the grafting rate of the maleic anhydride grafted polypropylene is 0.8-1.2%, and the grafting rate of the maleic anhydride grafted hydrogenated styrene-butadiene block copolymer is 1.0-2.0%.

[0007] Furthermore, the polypropylene is copolymer polypropylene, and the melt mass flow rate of the copolymer polypropylene is 8-12 g / 10 min.

[0008] Furthermore, the raw materials also include 3-6 parts of modified nanocellulose;

[0009] The modified nanocellulose is prepared by the following method:

[0010] (1) Dispersing expanded graphite uniformly in N-methylpyrrolidone, adding calcium carbonate, and stirring to obtain a mixture;

[0011] (2) Dissolving the nanocellulose in n-propanol, adding the mixture, ultrasonically dispersing, concentrating, drying, and crushing to obtain modified nanocellulose.

[0012] Furthermore, in step (1), the mass volume ratio of expanded graphite to N-methylpyrrolidine is 1.4-1.8 mg:1 mL, and the mass ratio of expanded graphite to calcium carbonate is 1:0.4-0.6.

[0013] Furthermore, in step (2), the mass volume ratio of nanocellulose to n-propanol is 1 mg:30-40 mL, the ultrasonic power in ultrasonic dispersion is 300-400 W, and the ultrasonic time is 40-50 min.

[0014] Furthermore, the tackifying resin is at least one of C5 petroleum resin (C5 resin), C9 petroleum resin (C9 resin), rosin resin or terpene resin;

[0015] The inorganic filler is at least one of talcum powder, barium sulfate or mica powder.

[0016] Furthermore, the polypropylene warm edge strip material further comprises 0.3-0.5 parts of an antioxidant;

[0017] The antioxidant is a mixture of antioxidants 168 and 1010 in a ratio of 1:1.

[0018] In a second aspect, the present invention provides a method for preparing the above-mentioned polypropylene warm edge strip, comprising the following steps:

[0019] (a) Weighing and setting aside the raw materials according to their proportions;

[0020] (b) The prepared raw materials are mixed, melted, extruded and granulated to obtain the polypropylene warm edge strip material.

[0021] In a third aspect, the present invention provides a warm edge strip, comprising the above-mentioned polypropylene warm edge strip material.

[0022] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0023] (1) The raw materials of the present invention are selected from maleic anhydride grafted PP, maleic anhydride grafted SEBS and tackifying resin in a specific ratio, which can increase the adhesion between the raw materials and stainless steel; at the same time, maleic anhydride grafted PP and maleic anhydride grafted SEBS can improve the dispersibility of the filler in the matrix resin, and the maleic anhydride grafted SEBS helps to improve the compatibility of PP and PS. Both PS and inorganic fillers can effectively improve the dimensional stability of the material, reduce the shrinkage ratio, and prevent the warm edge strip from separating steel from plastic during processing. The addition of PS is also conducive to the polar material being formed on the surface of the material during the molding process, further improving the interface bonding strength between steel and plastic;

[0024] (2) The expanded graphite and calcium carbonate in the nanocellulose modified by the method of the present invention increase the bonding force between the warm edge strip and the stainless steel. The nanoscale size and uniform dispersion of the modified nanocellulose make the contact area between it and the raw material of the warm edge strip larger, thereby increasing the bonding points and improving the peeling strength. The modified nanocellulose forms a tight network structure, reducing the shrinkage rate of the warm edge strip. Therefore, the addition of modified nanocellulose in the present invention significantly improves the peeling strength between the warm edge strip and the stainless steel, and also improves the hardness, heat resistance and chemical stability of the warm edge strip.

[0025] (3) In the present invention, due to the mutual synergy and joint action of the various components, the prepared warm edge strip can have excellent adhesion to stainless steel and high peel strength. At the same time, the product has good dimensional stability and a small shrinkage ratio, ensuring that the material is not prone to steel-plastic separation during the molding process.

[0026] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents particularly pointed out in the description. DETAILED DESCRIPTION

[0027] The following embodiments of the present invention are used to illustrate the principle of the present invention, but are not used to limit the scope of the present invention.

[0028] A specific embodiment of the present invention discloses a polypropylene warm edge strip material, wherein the polypropylene warm edge strip material comprises the following raw materials in parts by weight:

[0029] PP (polypropylene): 45-65 parts, for example, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts, 50 parts, 51 parts, 52 parts, 53 parts, 54 parts, 55 parts, 56 parts, 57 parts, 58 parts, 59 parts, 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts;

[0030] PS (polystyrene): 10-18 parts, for example, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts;

[0031] Maleic anhydride grafted PP (polypropylene): 4-8 parts, for example, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts;

[0032] Maleic anhydride grafted SEBS (hydrogenated styrene-butadiene block copolymer): 4-8 parts, for example, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts;

[0033] Tackifying resin: 8-12 parts, for example, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts;

[0034] Inorganic filler: 10-20 parts, for example, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts;

[0035] Lubricant: 0.2-0.4 parts, for example, 0.2 parts, 0.3 parts, 0.4 parts.

[0036] The raw materials of the present invention are selected from maleic anhydride grafted PP, maleic anhydride grafted SEBS and tackifying resin in a specific ratio, which can increase the adhesion between the raw materials and stainless steel; at the same time, the maleic anhydride grafted PP and the maleic anhydride grafted SEBS can improve the dispersibility of the filling in the matrix resin; the maleic anhydride grafted SEBS is helpful to improve the compatibility of PP and PS; both PS and inorganic filler can effectively improve the dimensional stability of the material, reduce the shrinkage ratio, and prevent the steel-plastic separation phenomenon of the warm edge strip during the processing; the addition of PS is also conducive to the polar material being formed on the surface of the material during the molding process, and further improves the interface bonding strength between the steel and the plastic.

[0037] In the present invention, due to the mutual synergy and joint action of the various components, it can be ensured that the prepared warm edge strip has excellent adhesion to stainless steel and has high peel strength. At the same time, the product has good dimensional stability and a small shrinkage ratio, ensuring that the material is not prone to steel-plastic separation during the molding process.

[0038] In a specific embodiment, the PP is a copolymer PP. Preferably, the copolymer PP is a block copolymer PP and / or a random copolymer PP. More preferably, the PP is a random copolymer PP.

[0039] Further preferably, the melt mass flow rate of the copolymer PP is 8-12 g / 10 min, for example, 8 g / 10 min, 9 g / 10 min, 10 g / 10 min, 11 g / 10 min, 12 g / 10 min.

[0040] After a large number of tests, it was found that when the melt mass flow rate of the copolymer PP is within the above range, the peel strength between the warm edge strip and stainless steel is higher and the shrinkage is lower.

[0041] In a specific embodiment, the PS is GPPS (general purpose polystyrene) and / or HIPS (high impact polystyrene). Preferably, PS is HIPS, which has better toughness.

[0042] In a specific embodiment, the maleic anhydride grafted PP is maleic anhydride grafted homopolymer PP and / or maleic anhydride grafted copolymer PP, preferably, the maleic anhydride grafted PP is maleic anhydride grafted copolymer PP. More preferably, the maleic anhydride grafted PP is a random copolymer PP with a grafting rate of 0.8-1.2%.

[0043] Preferably, the grafting rate of the maleic anhydride grafted PP is 0.8-1.2%, for example, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%.

[0044] In a specific embodiment, the grafting rate of the maleic anhydride grafted SEBS is 1.0-2.0%, for example, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, preferably, the grafting rate is 1.5-2.0%.

[0045] After a large number of tests, it was found that a suitable grafting ratio should be selected for the grafted product. If the grafting ratio is too low, the bonding strength will be reduced; if the grafting ratio is too high, the viscosity of the system will be increased, and uneven bonding will easily occur. Therefore, the maleic anhydride grafted PP and maleic anhydride grafted SEBS in the present invention select the above grafting ratio.

[0046] In a specific embodiment, the raw material also includes 3-6 parts of modified nanocellulose (for example, 3 parts, 3.2 parts, 3.4 parts, 3.6 parts, 3.8 parts, 4 parts, 4.2 parts, 4.4 parts, 4.6 parts, 4.8 parts, 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, 6 parts).

[0047] Wherein, the modified nanocellulose is prepared by the following method:

[0048] (1) Dispersing expanded graphite uniformly in N-methylpyrrolidone, adding calcium carbonate, and stirring to obtain a mixture;

[0049] (2) Dissolving the nanocellulose in n-propanol, adding the mixture, ultrasonically dispersing, concentrating, drying, and crushing to obtain modified nanocellulose.

[0050] The expanded graphite and calcium carbonate in the nanocellulose modified by the method of the present invention increase the bonding force between the warm edge strip and the stainless steel, and the nanometer size and uniform dispersion of the modified nanocellulose make the contact area between it and the raw material of the warm edge strip larger, thereby increasing the bonding points and improving the peeling strength. The nanocellulose modified by the present invention forms a tight network structure, reducing the shrinkage rate of the warm edge strip. Therefore, the peeling strength between the warm edge strip and the stainless steel is significantly improved after adding the modified nanocellulose in the present invention, and the hardness, heat resistance and chemical stability of the warm edge strip are also improved.

[0051] Specifically, in step (1), the mass volume ratio of expanded graphite to N-methylpyrrolidine is 1.4-1.8 mg:1 mL, for example, 1.4 mg:1 mL, 1.5 mg:1 mL, 1.6 mg:1 mL, 1.7 mg:1 mL, 1.8 mg:1 mL, and the mass ratio of expanded graphite to calcium carbonate is 1:0.4-0.6, for example, 1:0.4, 1:0.42, 1:0.44, 1:0.46, 1:0.48, 1:0.5, 1:0.52, 1:0.54, 1:0.56, 1:0.58, 1:0.6.

[0052] Specifically, in step (2), the mass volume ratio of nanocellulose to n-propanol is 1 mg:30-40 mL, for example, 1 mg:30 mL, 1 mg:32 mL, 1 mg:34 mL, 1 mg:36 mL, 1 mg:38 mL, 1 mg:40 mL.

[0053] Specifically, in step (2), the power of ultrasound in ultrasonic dispersion is 300-400 W, for example, 300 W, 310 W, 320 W, 330 W, 340 W, 350 W, 360 W, 370 W, 380 W, 390 W, 400 W, and the ultrasonic time is 40-50 min, for example, 40 min, 41 min, 42 min, 43 min, 44 min, 45 min, 46 min, 47 min, 48 min, 49 min, 50 min.

[0054] The modified nanocellulose in the present invention has a high specific surface area and excellent mechanical properties, can form a good interface interaction with the matrix material, and its fibrous structure can increase physical entanglement, improve the adhesion of the interface, thereby significantly improving the peel strength. Expanded graphite will expand rapidly when heated to form a worm-like structure. When it is added to the warm edge material, during the material processing, the expansion effect of the expanded graphite can fill the gaps inside the material, reduce the internal stress concentration of the material, and thus reduce the shrinkage ratio. At the same time, the lamellar structure of the expanded graphite can play a role in blocking and constraining the movement of molecular chains, further inhibiting the shrinkage of the material.

[0055] In a specific embodiment, the tackifying resin is at least one of C5 resin (C5 petroleum resin), C9 resin (C9 petroleum resin), rosin resin or terpene resin. Preferably, the tackifying resin is terpene resin.

[0056] In a specific embodiment, the inorganic filler is at least one of talc powder, barium sulfate or mica powder.

[0057] In a specific embodiment, the polypropylene warm edge strip further comprises 0.3-0.5 parts of an antioxidant.

[0058] In a specific embodiment, the antioxidant is a mixture of antioxidant 168 and antioxidant 1010 in a ratio of 1:1.

[0059] In a specific embodiment, the lubricant is PETS (pentaerythritol stearate).

[0060] Another specific embodiment of the present invention discloses a method for preparing the above-mentioned polypropylene warm edge strip, comprising the following steps:

[0061] (a) Weighing and setting aside the raw materials according to their proportions;

[0062] (b) The prepared raw materials are mixed, melted, extruded and granulated to obtain the polypropylene warm edge strip material.

[0063] In a specific embodiment, in step (b), the extrusion is carried out in a twin-screw extruder, and the temperature of zone 1 of the extruder is 150-160°C, the temperature of zone 2 is 170-180°C, the temperature of zone 3 is 180-190°C, the temperature of zone 4 is 200-210°C, the temperature of zone 5 is 200-210°C, the temperature of zone 6 is 200-210°C, and the temperature of zone 7 is 190-200°C.

[0064] In a specific embodiment, in step (b), the rotation speed of the screw is 320-360 r / min, and the feeding frequency is 25-35 Hz.

[0065] Another embodiment of the present invention discloses a polypropylene warm edge strip, which is made of the above-mentioned polypropylene warm edge strip material.

[0066] Another specific embodiment of the present invention discloses a method for preparing a polypropylene warm edge strip, comprising extruding a polypropylene warm edge strip material to obtain a polypropylene warm edge strip.

[0067] It should be noted that the bonding peel strength between the polypropylene warm edge strip and stainless steel of the present invention is ≥10N / mm, and the shrinkage rate of the material is ≤0.3%.

[0068] Preferably, the peel strength is 10-20 N / mm, for example, 10 N / mm, 10.2 N / mm, 10.4 N / mm, 10.6 N / mm, 10.8 N / mm, 11 N / mm, 11.2 N / mm, 11.4 N / mm, 11.6 N / mm, 11.8 N / mm, 12 N / mm, 12.2 N / mm, 12.4 N / mm, 12.6 N / mm, 12.8 N / mm, 13 N / mm, 13.5 N / mm, 14 N / mm, 14.5 N / mm, 15 N / mm , 15.5N / mm, 16N / mm, 16.5N / mm, 17N / mm, 17.5N / mm, 18N / mm, 18.5N / mm, 19N / mm, 19.5N / mm, 20N / mm, and the shrinkage rate is 0.14-0.29%, for example, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, and 0.30%.

[0069] The technical solution of the present invention is further explained below in conjunction with specific examples. All raw materials in the present invention are commercially available raw materials or prepared by existing methods.

[0070] Among them, the manufacturers and brands of some raw materials are shown in Table 1:

[0071]

[0072] Example 1

[0073] A polypropylene warm edge strip material of this embodiment includes the following raw materials in parts by weight: 49.3 parts of PP, 15 parts of PS, 5 parts of maleic anhydride grafted PP, 5 parts of maleic anhydride grafted SEBS, 10 parts of tackifying resin, 15 parts of inorganic filler, 0.4 parts of antioxidant and 0.3 parts of lubricant;

[0074] Among them, PP is a random copolymer PP with a melt mass flow rate of 10 g / 10 min, PS is HIPS, maleic anhydride grafted PP is a maleic anhydride grafted copolymer PP with a grafting rate of 1.0%, the grafting rate of maleic anhydride grafted SEBS is 1.5%, the tackifying resin is terpene resin, the inorganic filler is talcum powder, the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1, and the lubricant is PETS.

[0075] The preparation method of the polypropylene warm edge strip material of the present embodiment is as follows:

[0076] (a) According to the ratio of each raw material, weigh each raw material separately, put it into a high-speed mixer and mix it thoroughly to achieve a uniform mixing effect;

[0077] (b) Extruding the mixture in a twin-screw extruder after fine melting reaction and granulating. The temperature of the first zone of the extruder is 150-160°C, the temperature of the second zone is 170-180°C, the temperature of the third zone is 180-190°C, the temperature of the fourth zone is 200-210°C, the temperature of the fifth zone is 200-210°C, the temperature of the sixth zone is 200-210°C, the temperature of the seventh zone is 190-200°C, the speed of the screw is 320-360r / min, and the feeding frequency is 25-35Hz.

[0078] Example 2

[0079] A polypropylene warm edge strip material of this embodiment includes the following raw materials in parts by weight: 45 parts of PP, 18 parts of PS, 8 parts of maleic anhydride grafted PP, 8 parts of maleic anhydride grafted SEBS, 8 parts of tackifying resin, 12.3 parts of inorganic filler, 0.3 parts of antioxidant and 0.4 parts of lubricant;

[0080] Among them, PP is a block copolymer PP with a melt mass flow rate of 8 g / 10 min, PS is GPPS, maleic anhydride grafted PP is a maleic anhydride grafted homopolymer PP with a grafting rate of 0.8%, the grafting rate of maleic anhydride grafted SEBS is 1.0%, the tackifying resin is C5 resin, the inorganic filler is talcum powder, the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1, and the lubricant is PETS.

[0081] The preparation method of the polypropylene warm edge strip material in this embodiment is the same as that in Example 1.

[0082] Example 3

[0083] A polypropylene warm edge strip material of this embodiment includes the following raw materials in parts by weight: 63.3 parts of PP, 10 parts of PS, 4 parts of maleic anhydride grafted PP, 4 parts of maleic anhydride grafted SEBS, 8 parts of tackifying resin, 10 parts of inorganic filler, 0.5 parts of antioxidant and 0.2 parts of lubricant;

[0084] Among them, PP is a random copolymer PP with a melt mass flow rate of 12 g / 10 min, PS is HIPS, maleic anhydride grafted PP is a maleic anhydride grafted copolymer PP with a grafting rate of 1.2%, the grafting rate of maleic anhydride grafted SEBS is 2.0%, the tackifying resin is rosin resin, the inorganic filler is barium sulfate, the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a weight ratio of 1:1, and the lubricant is PETS.

[0085] The preparation method of the polypropylene warm edge strip material in this embodiment is the same as that in Example 1.

[0086] Example 4

[0087] The raw materials and preparation method of the polypropylene warm edge strip material of this embodiment are the same as those of Embodiment 1, except that the inorganic filler in the raw materials is mica powder.

[0088] Example 5

[0089] The raw materials and preparation method of the polypropylene warm edge strip material of this embodiment are the same as those of Example 1, except that the PP in the raw materials is block copolymer PP.

[0090] Example 6

[0091] The raw materials and preparation method of the polypropylene warm edge strip material of this embodiment are the same as those of Example 1, except that HIPS in the raw material is replaced by GPPS.

[0092] Example 7

[0093] The raw materials and preparation method of the polypropylene warm edge strip material of this embodiment are the same as those of Example 1, except that the terpene resin in the raw materials is replaced by C5 resin.

[0094] Example 8

[0095] The raw materials and preparation method of the polypropylene warm edge strip material of this embodiment are the same as those of Example 1, except that the maleic anhydride grafted copolymer PP in the raw materials is replaced by maleic anhydride grafted homopolymer PP.

[0096] Example 9

[0097] The raw materials and preparation method of the polypropylene warm edge strip material of this embodiment are the same as those of Example 1, except that the raw materials further include 4.5 parts of modified nanocellulose.

[0098] Wherein, the preparation method of modified nanocellulose is as follows:

[0099] (1) dispersing expanded graphite uniformly in N-methylpyrrolidone, wherein the mass volume ratio of expanded graphite to N-methylpyrrolidone is 1.6 mg:1 mL, adding calcium carbonate, wherein the mass ratio of expanded graphite to calcium carbonate is 1:0.5, and stirring to obtain a mixture;

[0100] (2) Dissolving the nanocellulose in n-propanol at a mass volume ratio of nanocellulose to n-propanol of 1 mg:35 mL, adding the mixture, and ultrasonically dispersing the mixture at a power of 350 W for 45 min, concentrating, drying, and crushing to obtain modified nanocellulose.

[0101] Example 10

[0102] The raw materials and preparation method of the polypropylene warm edge strip material of this embodiment are the same as those of Example 1, except that the raw materials also include 3 parts of modified nanocellulose. The preparation method of the modified nanocellulose is as follows:

[0103] (1) dispersing expanded graphite uniformly in N-methylpyrrolidone, wherein the mass volume ratio of expanded graphite to N-methylpyrrolidone is 1.4 mg:1 mL, adding calcium carbonate, wherein the mass ratio of expanded graphite to calcium carbonate is 1:0.4, and stirring to obtain a mixture;

[0104] (2) dissolving the nanocellulose in n-propanol at a mass volume ratio of nanocellulose to n-propanol of 1 mg:30 mL, adding the mixture, and ultrasonically dispersing the mixture at a power of 300 W for 50 min, concentrating, drying, and crushing to obtain modified nanocellulose.

[0105] Embodiment 11

[0106] The raw materials and preparation method of the polypropylene warm edge strip material of this embodiment are the same as those of Example 1, except that the raw materials further include 6 parts of modified nanocellulose.

[0107] Wherein, the preparation method of modified nanocellulose is as follows:

[0108] (1) dispersing expanded graphite uniformly in N-methylpyrrolidone, wherein the mass volume ratio of expanded graphite to N-methylpyrrolidone is 1.8 mg:1 mL, adding calcium carbonate, wherein the mass ratio of expanded graphite to calcium carbonate is 1:0.6, and stirring to obtain a mixture;

[0109] (2) dissolving the nanocellulose in n-propanol at a mass volume ratio of nanocellulose to n-propanol of 1 mg:40 mL, adding the mixture, ultrasonically dispersing at a power of 400 W for 40 min, concentrating, drying, and crushing to obtain modified nanocellulose.

[0110] Example 12

[0111] The raw materials and preparation method of the polypropylene warm edge strip material of this embodiment are the same as those of embodiment 2, except that the raw materials further include 4.5 parts of modified nanocellulose. The preparation method of the modified nanocellulose is the same as that of embodiment 9.

[0112] Embodiment 13

[0113] The raw materials and preparation method of the polypropylene warm edge strip material of this embodiment are the same as those of embodiment 3, except that the raw materials further include 4.5 parts of modified nanocellulose. The preparation method of the modified nanocellulose is the same as that of embodiment 10.

[0114] Comparative Example 1

[0115] The raw materials and preparation method of the polypropylene warm edge strip material in this comparative example are the same as those in Example 1, except that HIPS is not added to the raw materials, but is replaced by an equal weight portion of random copolymer PP, that is, the random copolymer PP is 64.3 parts.

[0116] Comparative Example 2

[0117] The raw materials and preparation method of the polypropylene warm edge strip material in this comparative example are the same as those in Example 1, except that maleic anhydride grafted copolymer PP is not added to the raw material, but is replaced by an equal weight portion of random copolymer PP, that is, the random copolymer PP is 54.3 parts.

[0118] Comparative Example 3

[0119] The raw materials and preparation method of the polypropylene warm edge strip material in this comparative example are the same as those in Example 1, except that maleic anhydride grafted SEBS is not added to the raw material, but is replaced by an equal weight portion of random copolymer PP, that is, the random copolymer PP is 54.3 parts.

[0120] Comparative Example 4

[0121] The raw materials and preparation method of the polypropylene warm edge strip material of this comparative example are the same as those of Example 1, except that terpene resin is not added to the raw materials, but is replaced by an equal weight portion of random copolymer PP, that is, the random copolymer PP is 59.3 parts.

[0122] Comparative Example 5

[0123] The raw materials and preparation method of the polypropylene warm edge strip material in this comparative example are the same as those in Example 1, except that talcum powder is not added to the raw material, but is replaced by an equal weight portion of random copolymer PP, that is, the random copolymer PP is 64.3 parts.

[0124] Comparative Example 6

[0125] The raw materials and preparation method of the polypropylene warm edge strip in this comparative example are the same as those in Example 1, except that the grafting rate of maleic anhydride grafted SEBS is 1.5%.

[0126] Comparative Example 7

[0127] The raw materials and preparation method of the polypropylene warm edge strip material in this comparative example are the same as those in Example 1, except that the grafting rate of the maleic anhydride grafted copolymer PP is 1.5%.

[0128] Comparative Example 8

[0129] The raw materials and preparation method of the polypropylene warm edge strip material in this comparative example are the same as those in Example 1, except that the filler in the raw materials is calcium carbonate.

[0130] Comparative Example 9

[0131] The raw materials and preparation method of the polypropylene warm edge strip material of this comparative example are the same as those of Example 1, except that the maleic anhydride grafted PP is 10 parts and the PP is 44.3 parts.

[0132] Comparative Example 10

[0133] The raw materials and preparation method of the polypropylene warm edge strip material of this comparative example are the same as those of Example 1, except that the maleic anhydride grafted SEBS is 2 parts and the PP is 52.3 parts.

[0134] Comparative Example 11

[0135] The raw materials and preparation method of the polypropylene warm edge strip material of this comparative example are the same as those of Example 9, except that the modified nanocellulose is replaced by nanocellulose.

[0136] Comparative Example 12

[0137] The raw materials and preparation method of the polypropylene warm edge strip material in this comparative example are the same as those in Example 9, except that no calcium carbonate is added during the preparation of the modified nanocellulose in this comparative example.

[0138] Comparative Example 13

[0139] The raw materials and preparation method of the polypropylene warm edge strip material of this comparative example are the same as those of Example 9, except that no expanded graphite is added during the preparation of the modified nanocellulose of this comparative example.

[0140] Comparative Example 14

[0141] The raw materials and preparation method of the polypropylene warm edge strip in this comparative example are the same as those in Example 1, except that the maleic anhydride grafted PP is replaced by maleic anhydride grafted APAO (amorphous α-olefin copolymer), and the manufacturer is Boluoke (Hangzhou) New Materials Co., Ltd.

[0142] Test Example 1

[0143] Warm edge strips were prepared using the polypropylene warm edge strips of Examples 1-13 and Comparative Examples 1-14 in accordance with the standard JC / T2453-2018 for insulating glass spacers, and were recorded as test samples 1-13 and control samples 1-14, respectively. The shrinkage of the warm edge strips was tested according to GB∕T15585-1995, and the peeling force between the warm edge strips and stainless steel was tested using a tensile testing machine. The results are shown in Table 2.

[0144]

[0145] From the table above, compared with the control sample 1 and the test sample 1, the warm edge strip prepared without HIPS in the raw material has poor performance. Since HIPS has better compatibility with terpene resin, it is more conducive to the uniform dispersion of the adhesive resin on the surface of the product during molding, which can further improve the adhesion between the product and stainless steel. In addition, the addition of HIPS can also significantly reduce the shrinkage ratio of the material. Compared with the test sample 6, HIPS can improve the peel strength more than GPPS.

[0146] Compared with the test sample 1, the control samples 2 and 3 can form a complementary graft structure by combining maleic anhydride grafted PP and maleic anhydride grafted SEBS, which can synergistically improve the adhesion between the warm edge olefin material and stainless steel.

[0147] Compared with the test sample 1, the control sample 4 can be evenly dispersed in the material after the addition of the tackifying resin, thereby increasing the adhesion between the entire system and the metal.

[0148] Compared with the test sample 1, the control sample 5 shows that the filler in the present invention can be evenly dispersed in the polypropylene material under the influence of maleic anhydride grafted PP and maleic anhydride grafted SEBS, which can greatly reduce the dimensional shrinkage of the material and has almost no negative impact on the peel strength of the product.

[0149] Compared with test sample 1, the grafting ratios of maleic anhydride grafted SEBS and maleic anhydride grafted copolymer PP in control samples 6 and 7 are not within the scope of the present invention, and the peel strength and shrinkage of the prepared warm edge strips are relatively poor.

[0150] Compared with test samples 1 and 4, the control sample 8 selected conventional calcium carbonate filler to prepare the warm edge strip has poor peel strength and shrinkage. The filler of the present application effectively improves the dimensional stability of the material, reduces the shrinkage ratio, prevents the steel-plastic separation phenomenon of the warm edge strip during processing, and improves the peel strength.

[0151] Compared with the test sample 1, the peel strength and shrinkage of the warm edge strips obtained by the control samples 9 and 10, which have the ratio of each raw material not within the scope of the present application, are relatively poor.

[0152] Compared with test samples 1-8, test samples 9-13 showed significantly increased peel strength and reduced shrinkage ratio after modified nanocellulose was added to the raw materials.

[0153] Compared with the test sample 1, the control sample 11 has almost no change in peel strength and shrinkage ratio after adding ordinary nanocellulose.

[0154] Compared with the test sample 9, the peel strength and shrinkage ratio of the control samples 12-13 did not change significantly when no calcium carbonate or expanded graphite was added to the modified nanocellulose.

[0155] Compared with the test sample 1, the control sample 14 has poor peel strength and shrinkage when the maleic anhydride grafted PP is replaced by maleic anhydride grafted APAO. This shows that the present invention selects maleic anhydride grafted PP, maleic anhydride grafted SEBS and tackifying resin in a specific ratio to increase the adhesion to stainless steel; at the same time, maleic anhydride grafted PP and maleic anhydride grafted SEBS can improve the dispersion of the filling in the matrix resin, and the maleic anhydride grafted SEBS helps to improve the compatibility of PP and PS. PS and inorganic fillers can effectively improve the dimensional stability of the material, reduce the shrinkage ratio, and prevent the warm edge strip from separating steel from plastic during processing. The addition of PS is also conducive to the polar material being formed on the surface of the material during the molding process, further improving the interface bonding strength between steel and plastic.

[0156] Based on the above analysis, the present invention selects specific raw materials and proportions. Under the mutual synergy and joint action of the various components, it can ensure that the prepared warm edge strip has excellent adhesion to stainless steel and has high peel strength. At the same time, the product has good dimensional stability and a small shrinkage ratio, ensuring that the material is not prone to steel-plastic separation during the molding process.

[0157] Test Example 2

[0158] Only the melt mass flow rate of the random copolymer PP in Example 1 was changed to investigate the effect of the melt mass flow rate on the peel strength and shrinkage of the warm edge strip. The specific test method was the same as that in Example 1. The results are shown in Table 3.

[0159]

[0160] It can be seen from the above table that when the melt mass flow rate is 8-12 g / min, the warm edge strip has a lower shrinkage ratio and a higher peel strength with stainless steel.

[0161] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A polypropylene warm edge strip, characterized in that: The polypropylene warm edge strip material comprises the following raw materials in parts by weight: polypropylene: 45-65 parts, HIPS: 10-18 parts, maleic anhydride grafted polypropylene: 4-8 parts, maleic anhydride grafted hydrogenated styrene-butadiene block copolymer: 4-8 parts, tackifying resin: 8-12 parts, inorganic filler: 10-20 parts, lubricant: 0.2-0.4 parts and modified nanocellulose: 3-6 parts; The grafting rate of the maleic anhydride grafted polypropylene is 0.8-1.2%, and the grafting rate of the maleic anhydride grafted hydrogenated styrene-butadiene block copolymer is 1.0-2.0%; The polypropylene is copolymer polypropylene, and the melt mass flow rate of the copolymer polypropylene is 8-12 g / 10 min; The modified nanocellulose is prepared by the following method: (1) Dispersing expanded graphite uniformly in N-methylpyrrolidone, adding calcium carbonate, and stirring to obtain a mixture; (2) dissolving the nanocellulose in n-propanol, adding the mixture, ultrasonically dispersing, concentrating, drying, and crushing to obtain modified nanocellulose; Wherein, in step (1), the mass volume ratio of expanded graphite to N-methylpyrrolidine is 1.4-1.8 mg:1 mL, and the mass ratio of expanded graphite to calcium carbonate is 1:0.4-0.6; In step (2), the mass volume ratio of nanocellulose to n-propanol is 1 mg:30-40 mL, the ultrasonic power in ultrasonic dispersion is 300-400 W, and the ultrasonic time is 40-50 min; The tackifying resin is at least one of C5 petroleum resin, C9 petroleum resin, rosin resin or terpene resin; The inorganic filler is at least one of talcum powder, barium sulfate or mica powder.

2. A polypropylene warm edge strip according to claim 1, characterized in that: The polypropylene warm edge strip material also includes 0.3-0.5 parts of antioxidant; The antioxidant is a mixture of antioxidants 168 and 1010 in a ratio of 1:

1.

3. A method for preparing the polypropylene warm edge strip according to claim 1 or 2, characterized in that: The steps include: (a) Weighing and setting aside the raw materials according to their proportions; (b) The prepared raw materials are mixed, melted, extruded and granulated to obtain the polypropylene warm edge strip material.

4. A warm edge strip, characterized in that: The invention comprises the polypropylene warm edge strip material as described in any one of claims 1 or 2.

Citation Information

Patent Citations

  • Method for preparing nanocellulose / polyvinyl alcohol hydrogel membrane with high ionic conductivity

    CN108641100A

  • Polypropylene material as well as preparation method and application thereof

    CN118222043A